Differential Regulation of Genes for Cyclic-di-GMP Metabolism Orchestrates Adaptive Changes During Rhizosphere Colonization by Pseudomonas fluorescens - Little, Richard H.; Woodcock, Stuart D.; Campilongo, Rosaria; Fung, Rowena K. Y.; Heal, Robert; Humphries, Libby; Pacheco-Moreno, Alba; Paulusch, Stefan; Stigliano, Egidio; Vikeli, Eleni; Ward, Danny; Malone, Jacob G. (Frontiers in Microbiology, 2019)
Bacteria belonging to the Pseudomonas genus are highly successful colonizers of the plant rhizosphere. The ability of different Pseudomonas species to live either commensal lifestyles or to act as agents of plant-growth promotion or disease is reflected in a large, highly flexible accessory genome. Nevertheless, adaptation to the plant environment involves a commonality of phenotypic outputs such as changes to motility, coupled with synthesis of nutrient uptake systems, stress-response molecules and adherence factors including exopolysaccharides. Cyclic-di-GMP (cdG) is a highly important second messenger involved in the integration of environmental signals with appropriate adaptive responses and is known to play a central role in mediating effective rhizosphere colonization. In this study, we examined the transcription of multiple, reportedly plant-upregulated cdG metabolism genes during colonization of the wheat rhizosphere by the plant-growth-promoting strain P. fluorescens SBW25. While transcription of the tested genes generally increased in the rhizosphere environment, we additionally observed a tightly orchestrated response to environmental cues, with a distinct transcriptional pattern seen for each gene throughout the colonization process. Extensive phenotypical analysis of deletion and overexpression strains was then conducted and used to propose cellular functions for individual cdG signaling genes. Finally, in-depth genetic analysis of an important rhizosphere colonization regulator revealed a link between cdG control of growth, motility and stress response, and the carbon sources available in the rhizosphere.